MUTU ORGANOLEPTIK DAN KOMPOSISI GIZI SOSIS TETELAN IKAN TUNA (Thunnus sp) - Loppies, Cindy R. M.; Tomia, Asnawati; Nanlohy, Esterlina E. E. M. (Pattimura University, 2024)
Tuna swallow contains high protein but has the disadvantage of smelling fishy. Tuna swallow is usually sold cheaply and is underutilized, while its potential is quite large. Therefore it is necessary to diversify processed fishery products to increase the utilization or added value of tuna fish, one of which is the manufacture of fish sausages. The purpose of this study was to determine the organoleptic quality and nutritional composition of tuna fish sausage (Thunnus sp).The study used an experimental method with three different concentrations of tuna fillet meat to obtain the physical form and good quality content of tuna fish sausage based on organoleptic test results and nutritional content test results using the proximate analysis method. Based on the results of the research on the best organoleptic quality, there was treatment A1 with an appearance value of 7.6, smell of 7.1, taste of 7.4 and texture of 7.0. While the best proximate value or nutritional composition is found in A3 with a value of 19.9% ​​protein content, 1.4% fat content, 7.2% carbohydrate content, 70.4% water content and 0.8% ash content.